2017
DOI: 10.1016/j.polymer.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dispersion and properties of a two-component epoxy nanocomposite using surface modified cellulose nanocrystals

Abstract: Epoxy nanocomposites reinforced with acetyl, hexanoyl, and dodecanoyl surface modified Cellulose Nanocrystals (CNC) were fabricated. Surface modified CNCs were dispersed in epoxy resin with a co-solvent. After complete removal of the co-solvent, a typical two component epoxy system was achieved where hardener was then added to cure the resin. Acetyl grafted CNC (CNC_a) and hexanoyl grafted CNC (CNC_h) both had good dispersion in cured epoxy as observed visually and through electron microscopy. Tensile modulus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…The mechanical features of this kind of nanocomposites are deeply affected by the interfacial adhesion between CNCs and the polymer matrix, which can enhanced by caring out specific modifications on these components (Gopi et al, 2019). On the other hand, the combination of CNCs and thermosets (unsaturated polyesters, some polyurethanes, epoxy and phenolic resins) in nanocomposites aims to couple attractive features from each compound in a synergetic manner (Peng et al, 2017;Yue et al, 2018). CNCs provide better strength and stiffness along with resistance to corrosion.…”
Section: Nanocellulose Based Nanocompositesmentioning
confidence: 99%
“…The mechanical features of this kind of nanocomposites are deeply affected by the interfacial adhesion between CNCs and the polymer matrix, which can enhanced by caring out specific modifications on these components (Gopi et al, 2019). On the other hand, the combination of CNCs and thermosets (unsaturated polyesters, some polyurethanes, epoxy and phenolic resins) in nanocomposites aims to couple attractive features from each compound in a synergetic manner (Peng et al, 2017;Yue et al, 2018). CNCs provide better strength and stiffness along with resistance to corrosion.…”
Section: Nanocellulose Based Nanocompositesmentioning
confidence: 99%
“…[ 35 ] Peng et al. [ 36 ] showed that better dispersion of covalently modified CNCs in an amine crosslinked epoxy matrix resulted in a higher Young's modulus, tensile strength, and work of fracture. However, in water‐based preparation methods, the dispersion state of CNCs and their interactions with polymer particles also influence their spatial arrangement in the dried films and thus, their impact on physical properties.…”
Section: Figurementioning
confidence: 99%
“…Composite containing 0.2 wt% modified CNCs exhibits enhancements of tensile strength (77%) and modulus (44%). Peng et al [117] studied the influence of alkane chain length on the dispersibility of modified CNCs in epoxy. CNCs modified by acetyl and hexanoyl show good dispersibility, thereby improving the mechanical properties of nanocomposites.…”
Section: Esterification Of Cellulosementioning
confidence: 99%